PENGEMBANGAN SISTEM IOT UNTUK MEMONITORING SUHU TUBUH DENYUT JANTUNG DAN SATURASI OKSIGEN PADA TUBUH MANUSIA - Ilham, Muhammad Farhan; Agustina, Merry (Infotech: Journal of Technology Information, 2025)
This research aims to design Internet of Things (IoT) based medical devices that can monitor body temperature, heart rate and oxygen saturation. The problem faced is the lack of real-time health monitoring tools that are integrated with digital systems, especially during the pandemic. As a solution, this tool utilizes the MLX90614 sensor to measure body temperature, the MAX30100 sensor for heart rate and oxygen saturation, and the ESP8266 microcontroller to connect the device to a Wi-Fi network. The method used is system development using the Waterfall model, starting from needs analysis, design, implementation, to testing. A threshold algorithm is applied to detect abnormal values in sensor data, which is then sent to the server and displayed via a web interface. Test results show that this tool can monitor health conditions accurately and in real-time. Data on body temperature, heart rate and oxygen saturation are stored in a database and displayed via the web with a fast response. This tool is expected to help users in monitoring health more efficiently and easily to use.